2022
DOI: 10.1002/mgg3.2066
|View full text |Cite
|
Sign up to set email alerts
|

The effect of growth hormone treatment in children with novel BPTF gene variants: A report of two cases and literature review

Abstract: BPTF gene (OMIM*601819) encodes the bromodomain PHD finger transcription factor (BPTF), the largest unit of nucleosome remodeling factor, which regulates chromatin remodeling (Stankiewicz et al., 2017). BPTF plays a key role in the differentiation of the primary germ layers and the establishment of the embryonal anterior-posterior axis (Landry et al., 2008). The BPTF gene is located on chromosome 17q24.2. The haploinsufficiency of human BPTF is known to cause neurodevelopmental disorder with dysmorphic facies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…4B), which further highlighted the essential role of dopamine in neurodevelopment as a key neurotransmitter. For example, these neurodevelopment-related proteins included zinc finger protein 609 (ZNF609), 34 tuberous sclerosis complex 2 (TSC2), 35 RE1-silencing transcription factor (REST), 36 polyglutamine-binding protein 1 (PQBP1), 37 centromere protein F (CENPF), 38 nucleosome-remodeling factor subunit BPTF (BPTF), 39 muscleblind-like protein 1 (MBNL1), 40 etc. Additionally, there were other important regulators in neurobiology identified, including axin-1 (AXIN1) that participates in the blood-brain barrier (BBB) protection and improvement of neurological functions during ischemic stroke.…”
Section: ) Distinct Stratification Among Different Groups Was Observe...mentioning
confidence: 99%
“…4B), which further highlighted the essential role of dopamine in neurodevelopment as a key neurotransmitter. For example, these neurodevelopment-related proteins included zinc finger protein 609 (ZNF609), 34 tuberous sclerosis complex 2 (TSC2), 35 RE1-silencing transcription factor (REST), 36 polyglutamine-binding protein 1 (PQBP1), 37 centromere protein F (CENPF), 38 nucleosome-remodeling factor subunit BPTF (BPTF), 39 muscleblind-like protein 1 (MBNL1), 40 etc. Additionally, there were other important regulators in neurobiology identified, including axin-1 (AXIN1) that participates in the blood-brain barrier (BBB) protection and improvement of neurological functions during ischemic stroke.…”
Section: ) Distinct Stratification Among Different Groups Was Observe...mentioning
confidence: 99%
“…Intriguingly, even though the colon cancer cell line was utilized as a model in this research, within the cluster of identified 176 dopaminylated proteins that are associated with RNA splicing and nucleic acid-templated transcription, a subset was discovered to be linked to nervous system development (Figure B), which further highlighted the essential role of dopamine in neurodevelopment as a key neurotransmitter. For example, these neurodevelopment-related proteins included zinc finger protein 609 (ZNF609), tuberous sclerosis complex 2 (TSC2), RE1-silencing transcription factor (REST), polyglutamine-binding protein 1 (PQBP1), centromere protein F (CENPF), nucleosome-remodeling factor subunit BPTF (BPTF), and muscleblind-like protein 1 (MBNL1) . Additionally, there were other important regulators in neurobiology identified, including axin-1 (AXIN1) that participates in the blood–brain barrier (BBB) protection and improvement of neurological functions during ischemic stroke .…”
Section: Resultsmentioning
confidence: 99%
“…Further supporting a function in height, mutations in BPTF in humans are associated with neurodevelopmental disorder with dysmorphic facies and distal limb anomalies (NEDDFL), a rare disease that causes short stature, among other clinical features. 7 …”
Section: Main Textmentioning
confidence: 99%